Exploring nocturnal soundscapes in an Australian open forest system using acoustic indices - Felipe do Carmo Jorge; Gabriel Politzer Couto; Berndt J. Van Rensburg (PLoS ONE, 2026)
Nocturnal environments and their ecology remain noticeably under-represented in the scientific literature, despite their ecological importance, largely due to the practical challenges of sampling nighttime ecology. Passive acoustic monitoring provides a cost-effective, scalable tool for extracting ecological insights from continuous recordings, using acoustic indices. This study assessed whether a suite of acoustic indices can capture the diversity of nighttime calls (i.e., sonotype richness used here as a proxy for biodiversity) in a terrestrial ecosystem. Our main findings supported an interaction effect of indices (acoustic activity (ACT), acoustic evenness (AEI), spectral entropy (Hf), soundscape saturation (Sm)) correlating best with variation in sonotype richness. This result was further supported by habitat-dissimilarity analyses based on manually tagged insect sonotype richness compared to index values showing significant similarities. Although the methodological framework used in this study is adaptable to other environments, index performance is unlikely to be directly transferable due to differences in vocal assemblages and background noise conditions. Overall, the study provides a useful procedure to track patterns in nighttime ecology and support the evaluation of the state of nighttime ecology.